Preferential Generation of 15-HETE-PE Induced by IL-13 Regulates Goblet Cell Differentiation in Human Airway Epithelial Cells - Zhao, Jinming; Minami, Yoshinori; Etling, Emily; Coleman, John M.; Lauder, Sarah N.; Tyrrell, Victoria; Aldrovandi, Maceler; O’Donnell, Valerie; Claesson, Hans-Erik; Kagan, Valerian; Wenzel, Sally (American journal of respiratory cell and molecular biology, 2017)
Type 2-associated goblet cell hyperplasia and mucus hypersecretion are well known features of asthma. 15-Lipoxygenase-1 (15LO1) is induced by the type 2 cytokine IL-13 in human airway epithelial cells (HAECs) in vitro and is increased in fresh asthmatic HAECs ex vivo. 15LO1 generates a variety of products, including 15-hydroxyeicosatetraenoic acid (15-HETE), 15-HETE-phosphatidylethanolamine (15-HETE-PE), and 13-hydroxyoctadecadienoic acid (13-HODE). In this study, we investigated the 15LO1 metabolite profile at baseline and after IL-13 treatment, as well as its influence on goblet cell differentiation in HAECs. Primary HAECs obtained from bronchial brushings of asthmatic and healthy subjects were cultured under air-liquid interface culture supplemented with arachidonic acid and linoleic acid (10 μM each) and exposed to IL-13 for 7 days. Short interfering RNA transfection and 15LO1 inhibition were applied to suppress 15LO1 expression and activity. IL-13 stimulation induced expression of 15LO1 and preferentially generated 15-HETE-PE in vitro, both of which persisted after removal of IL-13. 15LO1 inhibition (by short interfering RNA and chemical inhibitor) decreased IL-13-induced forkhead box protein A3 (FOXA3) expression and enhanced FOXA2 expression. These changes were associated with reductions in both mucin 5AC and periostin. Exogenous 15-HETE-PE stimulation (alone) recapitulated IL-13-induced FOXA3, mucin 5AC, and periostin expression. The results of this study confirm the central importance of 15LO1 and its primary product, 15-HETE-PE, for epithelial cell remodeling in HAECs.